Research progress of Management of acute skin failure in critically ill patients (重症患者急性皮肤衰竭管理的研究进展) - YUAN Yingying (袁迎迎); GAO Qian (高倩) (中西医结合护理)
This paper reviewed the studies on differences between acute skin failure and pressure injuries, risk factors, evaluation, integration management and wound care of acute skin failure in critically ill patients. Nurses should correctly identify patients at high risk of acute skin failure and carry out early preventive measures. (本文对重症患者急性皮肤衰竭与压力性损伤的差异、危险因素、评估、整体管理及伤口管理进行综述。医务人员应正确识别急性皮肤衰竭的高危患者, 早期预防和干预, 以降低急性皮肤衰竭的危害。)